The lowest canonical denominator: electronic literary texts, and the role of the information professional - Claire Warwick (Information Research: An International Electronic Journal)
This paper argues that the English literary canon has reasserted itself in electronic form. It traces the history of print canons and contends that analogous forces are shaping an electronic canon. This issue should concern not only literary critics, but also information professionals. Humanities scholars need diverse resources, rare texts and multiple editions of works. Yet canons threaten diversity of resources, and it is difficult for works to re-establish their place once excluded. If Collection managers aim to provide a wide range of high quality resources for future users then an electronic canon is undesirable. If we are to avoid such problems then questions of electronic collections policy must be addressed. For example, do funding councils bear a responsibility to ensure that less canonical texts are available? Who makes the decisions about what is important, and on what basis? How should electronic collections policies be formulated? Should the choice of editions which are digitised matter, is a bad edition better than nothing at all? Should collections policy for electronic resources be organised on a national level, or left to individual institutions? These are areas in which in information professional can and should be able to make an important contribution.